Exploring the Influence of Online Consumer Reviews on Sales of Umrah Travel Agencies: The Moderating Role of Package Pricing - Harun, Amran; Ishak, Muhamad Izaidi; Muslim, Much Aziz (International Review of Management and Marketing, 2025)
This study aims to investigate the influence of online consumer reviews on the sales of Umrah travel agencies, with the Umrah package price serving as a moderator. The sample included 82 of the 296 registered Malaysian Umrah travel agencies. Secondary data on online consumer reviews were obtained from the Google Reviews and matched with the 2019 sales data of these agencies. Partial Least Squares Structural Equation Modeling was applied for data analysis. The results reveal that the reviewer expertise positively influences the sales of Umrah travel agencies. Surprisingly, identity disclosure was found to be insignificant. Additionally, the findings demonstrate the positive moderating effect of Umrah package price on this relationship. This study suggests that Umrah travel agencies encourage past customers to leave feedback on Google Reviews to increase the presence of expert reviewers. Additionally, leveraging online consumer reviews can help agencies engage with consumers, particularly when promoting premium Umrah packages.